Heuristic biases on perceived market efficiency case of Indonesia - Latifah Wulandari Binti Asbaruna; Ridwan Ismail Gorib (Institute of Computer Science (IOCS), 2023)
Understanding human behavior is the key to behavioral finance's significance in the financial world. The majority of research focuses on financial markets that are well-developed, and little is known about heuristic biases in the perception of market efficiency in emerging nations like Indonesia. The data collection technique in this research is a literature study that is directly related to heuristic bias in perceived market efficiency. Investors’ heuristic biases have been measured using a questionnaire, containing numerous items, including indicators of speculators, investment decisions and perceived market efficiency variables. The sample consists of 150 investors trading on the BEI. A convenient, purposively sampling technique was used for data collection. To examine the relationship between heuristic biases, investment decisions and perceived market efficiency, hypotheses were tested by using correlation and regression analysis. Additionally, the research aims to forecast future directions in the field of behavioral finance, with the ultimate goal of offering fresh perspectives and insights into the field. This may encourage future research on heuristic biases in perceived market efficiency.